Revelation and religion in Levinas - Fernández Hart, Rafael (Estudios de Filosofía, 2018)
This article proposes a descriptive analysis of Levinas’s work based on the term ‘revelation’. The clarication of the term requires understanding the two sources which Levinas makes converse: the Bible and the philosophers. In this dialogue, Levinas uses phenomenology to show how the phenomenological consciousness is interrupted by the Infinite. In this sense, dealing with this disruption shall imply both thinking about the essence of human being and describing its spirituality: the spirituality of human being is expressed as an ethical endeavor. The article aims to show that the scope of the Levinasian thesis about revelation allows the concept of religion update, that is, to sketch a new philosophy of religion as an ethical mandate, therefore, avoiding any confusion with theological work.